The Implementation of Green Facades towards the Establishment of Sustainable Green Buildings, Leading to Environmentally Responsible Urban Architecture and Design - Jain, Anshul; Babu, Ananda (Urban Planning and Construction, 2025)
Green facades, integrating vegetation into building envelopes, are a pivotal strategy for sustainable urban architecture, addressing challenges like urban heat islands, energy inefficiency, and biodiversity loss. This comprehensive review synthesizes global research, evaluating green facades’ environmental benefits, including thermal regulation, air quality improvement, and biodiversity enhancement, alongside their economic viability and social impacts. Through detailed case studies and performance analyses, the paper highlights their transformative role in sustainable green buildings and urban design. Challenges, such as high costs, maintenance demands, and climate adaptability, are critically assessed, alongside innovative technological and policy solutions to scale adoption. The findings underscore green facades as a cornerstone of environmentally responsible urban futures, aligning with global sustainability goals like the United Nations Sustainable Development Goals (SDGs).